Running momentum: A new method to quantify prolonged high-intensity intermittent running performance in collision sports - Scott, T. J.; Dascombe, B. J.; Delaney, J. A.; Sanctuary, C. E.; Scott, M. T. U.; Hickmans, J. A.; Duthie, G. M. (Science and Medicine in Football, 2017)
Purpose: This study determined differences in prolonged high-intensity running (PHIR) performance and running momentum (pIFT) between competition levels and positional groups in rugby league. Methods: Elite Australian National Rugby League (NRL), sub-elite [state-based competition (SRL); National Youth Competition (NYC); local league (LL)] and junior-elite (U18; U16) rugby league players completed the 30-15 Intermittent Fitness Test (30-15IFT) to quantify PHIR performance. Final running momentum (pIFT; kg·m/s) was calculated as the product of body mass and final running velocity (VIFT; m/s). Effect sizes (ESs) were used to examine between-group differences. Results: 30-15IFT performance was possibly to likely higher in NRL players (19.5 ± 1.0 km/h; mean ± SD) when compared with SRL (ES = 0.6 ± 0.5; ES ± CI), NYC (ES = 0.6 ± 0.5) and U18 (ES = 0.8 ± 0.5) players. NRL players (537 ± 41 kg·m/s) possessed possibly to very likely greater pIFT than SRL (ES = 0.7 ± 0.5), NYC (ES = 1.2 ± 0.5), U18 (ES = 2.3 ± 0.6), U16 (ES = 3.0 ± 0.7) and LL players (ES = 2.0 ± 0.7). Middle forwards attained a likely superior pIFT (ES = 0.5 - 1.8) to all other positional groups. Conclusions: This study demonstrated that elite rugby league players possess superior PHIR capacities, whilst highlighting that pIFT can account for the disparities in body mass between groups.